IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU BERDASARKAN SISTEM ZONASI PADA TAHUN PELAJARAN 2019/2020 DI KOTA PEKANBARU - Chika Virginia Novri Utari; Hasim As’ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The zoning system is a new student admissions process system that looks at the distance between the residence of prospective students and the school. With the zoning system can create a level of quality education and fairness as a synergy and integration of education development services. In Pekanbaru, a new admissions policy based on the zoning system has been implemented in every school, especially at the state junior high school level in Pekanbaru. However, in the application of admission of new students using the provisions of the zoning system reaped problems that included the percentage of admissions of new students zoning pathways below 90% of the provision stipulated. Therefore, researchers are interested in conducting research related to the implementation of new student acceptance policies based on zoning systems. The purpose of this study is to know the process of implementing a new student admissions policy based on the zoning system in the 2019/2020 school year in Pekanbaru city and to know the factors that affect in the implementation of the admissions policy of new students based on the zoning system. The theory used in this study is the theory of policy implementation by Van Meter and Van Horn. To be able to answer these problems researchers used qualitative methods with a descriptive approach. In this qualitative study the authors used data collection techniques in the form of observations, interviews and documentation then analyzed based on research problems. The results of this study show that the implementation of a new student admissions policy based on the zoning system in 2019/2020 in Pekanbaru city has not gone well due to several factors affecting the implementation of this zoning system, namely related to infrastructure, socialization and public opinion. Keywords: Policy Implementation, New Student Admission, Zoning System